Safety and Outcome of Carotid Dissection Stenting During the Treatment of Tandem Occlusions: A Pooled Analysis of TITAN and ETIS. Issue 12 (December 2020) - Marnat, Gaultier; Lapergue, Bertrand; Sibon, Igor; Gariel, Florent; Bourcier, Romain; Kyheng, Maeva; Labreuche, Julien; Dargazanli, Cyril; Consoli, Arturo; Blanc, Raphael; Piotin, Michel; Mazighi, Mikael; et al.
Abstract : Background and Purpose: The efficacy of endovascular therapy in patients with acute ischemic stroke due to tandem occlusion is comparable to that for isolated intracranial occlusion in the anterior circulation. However, the optimal management of acute cervical internal carotid artery lesions is unknown, especially in the setting of carotid dissection, but emergency carotid artery stenting (CAS) is frequently considered. We investigated the safety and efficacy of emergency CAS for carotid dissection in patients with acute stroke with tandem occlusion in current clinical practice. Methods: We retrospectively analyzed a prospectively maintained database composed of 2 merged multicenter international observational real-world registries (Endovascular Treatment in Ischemic Stroke and Thrombectomy in Tandem Lesion). Data from endovascular therapy performed in the treatment of tandem occlusions related to acute cervical carotid dissection between January 2012 and January 2019 at 24 comprehensive stroke centers were analyzed. Results: The study assessed 136 patients with tandem occlusion due to dissection, including 65 (47.8%) treated with emergency CAS and 71 (52.2%) without. The overall rates of favorable outcome (90-day modified Rankin Scale score, 0–2) and successful reperfusion (modified Thrombolysis in Cerebral Infarction, 2b–3) were 58.0% (n=76 [95% CI, 49.6%–66.5%]) and 77.9% (n=106 [95% CI, 71.0%–85.0%]), respectively. In subgroup analyses, the rate of successful reperfusion (89.2% versus 67.6%; adjusted odds ratio, 2.24 [95% CI, 1.33–3.77]) was higher after CAS, whereas the 90-day favorable outcome (54.3% versus 61.4%; adjusted odds ratio, 0.84 [95% CI, 0.58–1.22]), symptomatic intracerebral hemorrhage (sICH; 10.8% versus 5.6%; adjusted odds ratio, 1.59 [95% CI, 0.79–3.17]), and 90-day mortality (8.0% versus 5.8%; adjusted odds ratio, 1.00 [95% CI, 0.48–2.09]) did not differ. In sensitivity analyses of patients with successful intracranial reperfusion, CAS was not associated with an improved clinical outcome. Conclusions: Emergency stenting of the dissected cervical carotid artery during endovascular therapy for tandem occlusions seems safe, whatever the quality of the intracranial reperfusion. Abstract : Supplemental Digital Content is available in the text.